Estimation of ozone and peroxide levels in the air of Croatia - Pehnec, Gordana (Array, 2009)
Summary: Volume fractions of different atmospheric gas constituents were modelled using Master Mechanism (MM) model developed by S. Madronich (NCAR, Boulder, CO, USA). Ozone (O3) and hydrogen peroxide (H2O2) seasonal variations were estimated at three different locations in Zagreb. Modelled ozone values showed good agreement with measured values at all three sites. The estimation of H2O2 annual variations with the MM model showed typical H2O2 seasonal variation at a remote location and at an urban location not exposed to traffic, with the highest values over the summer months, due to higher solar radiation. The summer/winter differences were more pronounced at the remote location. At the site exposed to traffic, H2O2 volume fractions did not show seasonal variations and H2O2 levels were determined by the levels of nitrogen oxides. The model was also used to estimate oxidant levels during the heat wave in August 2003. It yielded high hydrogen peroxide (2.5 ppb–3.5 ppb) and ozone (> 100 ppb) levels, followed by increased concentrations of OH radicals. The model confirmed that in extreme conditions (high temperature and solar radiation, elevated CO and NO2 levels) over the summer, the atmospheric oxidizing capacity in Croatia exceedingly rises and may exert harmful effects on the environment